Priming bumble bees with caffeine, odour of the target crop, and a food reward, has minimal effects on fruit crop pollination and yield in a semi-commercial setup - Sarah Arnold; Celine Silva; Jan-Hendrik Dudenhöffer; David Hall; Dudley Farman; Felix Wäckers; Philip Stevenson; Michelle Fountain (Journal of Pollination Ecology)
Caffeine is a widely occurring plant defence chemical that occurs in the nectar of some plants, e.g. Coffea or Citrus spp., where it may influence pollinator behaviour to enhance pollination. Previous laboratory work found inexperienced bumblebees (Bombus terrestris) located new food sources emitting a learned floral odour more consistently if they had been fed caffeine in association with the odour and a food reward. Inexperienced bees primed with caffeine also made more initial visits to target robotic flowers emitting the target odour, compared to control bees or those primed with odour alone.